(untitled) (Baghdad Science Journal, 2019)
Peroxidase is a class of oxidation-reduction reaction enzyme that is useful for accelerating many oxidative reactions that protect cells from the harmful effects of free radicals. Peroxidase is found in many common sources like plants, animals and microbes and have extensive uses in numerous industries such as industrial, medical and food processing. In this study, P. aeruginosa was harvested to utilize and study its peroxidases. P. aeruginosa was isolated from a burn patient, and the isolate was verified as P. aeruginosa using staining techniques, biochemical assay, morphological, and a sensitivity test. The gram stain and biochemical test result show rod pink gram-negative bacteria, and ensure that the isolate was that of P. aeruginosa. Optimization for bacterial growth were done by used more than pH (5,7,9) and temperatures (32,35,37°C), and it was found that the best growth conditions were at pH 5.5, producing (4.5x108cells), and a temperature of 37°C, with (5.25x108cells) being produced. Intracellular enzymes were extracted by ultra-sonication that used frequencies of ultrasound 30 kHz for 20 min in 4 °C, and was centrifuged at 13000×g for 5min. The supernatant was then re-used as a crude enzymatic extract and the cell pellet was discarded. Purification of peroxidase was accomplished by using salt precipitation, dialysis, gel filtrations and ion exchange chromatographic techniques. The result shows that gel filtration has optimal specific activity and purification fold at (61 U/ml), purification fold 6 times and then the improvement enzyme was applied as H2O2 scavenging activity antioxidant by used three concentration of enzyme (10,40,60 µg/ml), and show higher scavenging activity at 60 µg/ml, which reached to 45% scavenging activity. The enzyme was also used as anticancer agent, which was verified by using three concentration of enzyme (10,15,20 µg/ml) which show a significant kill for Mcf-7cells at (15µg/ml), with cytotoxicity activity reaching (45%).